Lanthanum plumbide as a new neutron multiplier material - Ramil Gaisin; Pavel Pereslavtsev; Siegfried Baumgaertner; Klaus Seemann; Elvina Gaisina; Vladimir Chakin; Sergey Udartsev; Pavel Vladimirov; Bronislava Gorr (Journal of Materials Research and Technology, 2023)
A new neutron multiplier based on lanthanum plumbide LaPb3 was produced using two different casting methods. The argon-arc melted material consists of LaPb3 dendrites between grains of LaPb2 phase of approximately equal volume fraction. The induction melted material is composed primarily of large LaPb3 grains, about 80 μm in size. Corrosion testing at 20 and 300 °C in air revealed the rapid degradation of LaPb3 without the formation of a protective passivation layer. The corrosion process results in significant volumetric expansion accompanied by cracking. When LaPb3 is exposed to air at 500 °C, pure lead as a corrosion product melts to form layers protecting against rapid corrosion. LaPb3 showed low (113–193 MPa), but sufficient strength for functional use in the temperature range of 20–500 °C.